On a New Inequality Applicable to Certain Volterra-Fredholm Type Sum-difference Equations - Pachpatte, B. G.
The aim of the present paper is to establish a new finite difference inequality with explicit estimate which can be used as a tool in the study of some basic properties of solutions of certain Volterra-Fredholm type sum-difference equations.
Keywords: Finite difference inequality; Volterra-Fredholm type; Sum-difference equations; Numerical methods